Análise do desempenho térmico de um sistema de aquecimento solar de baixo custo - Lopo, Alexandre Boleira (2010)
It presents a solar collector to be used in a system for heating water for bathing, whose main characteristics are low cost and easy manufacturing and assembly. The system operates under natural convection or thermosiphon. The absorbing surface of the collector is formed by twelve PVC pipes of 25 mm outside diameter connected in parallel via connections in T of the same material. The tubes were covered with absorbing fins made with recycled aluminum cans. We studied eight settings between absorber plate, thermal insulating EPS boards and thermal reservoirs 150 and 200 liters. It was determined the most efficient configuration for the correct purpose. We evaluated thermal parameters that proved the viability of the heating system studied